Comparison of the catalytic properties of SOFC anode supports under dry reforming of methane - Guerra,C; Lanzini,A; Leone,P; Santarelli,M; Smeacetto,F; Fiorili,S; Gondolini,A; Mercadelli,E; Sanson,A; Brandon,NP (2013)
The work investigates the catalytic properties of different SOFC anode substrates towards the chemical conversion of methane and carbon dioxide into H2 and CO-rich mixtures. The analysis is carried out by means of experiments in micro-reactor configuration. A mass spectrometer is provided to analyze the composition of the gas mixture leaving the reactor and thus allowing the evaluation of methane conversion rate. Furthermore, Temperature Programmed Oxidation (TPO) experiments are performed on the anode samples aiming at the analysis of material activity towards the cracking reaction of methane. Anode substrates based on different materials and microstructures are taken into account. The work features the effect of materials' composition and microstructure on the methane conversion rate and carbon cracking.